Research on power grid expansion planning method based on multi-party competition considering security margin - CHEN Yongshu; HONG Haisheng; TANG Xian; ZHOU Xianhua; LI Ronglin (Diance yu yibiao)
Power grid expansion is often carried out under multiple scenarios, and the benefits and security margins brought to the power grid by different scenarios are not consistent. Therefore, this paper proposes a multi-party competitive planning method to balance grid security and investment returns. A mathematical model of power grid expansion planning with multiple investors is developed, and the concept of Nash equilibrium is used to model the grid planning game as an equilibrium problem with equilibrium constraints (EPEC). The EPEC is modeled as a mixed integer linear programming problem through a series of linearization. The energy shortage probability is used as a security margin assessment criterion to model the risk of uncertain operating parameters in the grid planning game. By modeling the security margin, the Nash equilibrium of the grid planning game under different risk levels can be obtained. The results of the grid investment game may differ from the social benefit maximization benchmark model. In addition, a support budget mechanism is designed to incentivize the investors so that the results of the grid planning game are as close as possible to the social benefit maximization results. The proposed approach is evaluated on two scales of systems, and the test results show that the proposed approach can bring the equilibrium point of the non-cooperative game closer to the point with smaller social cost, which verifies its effectiveness.